SDHC mutation in an elderly patient without familial antecedents - López-Jiménez, Elena; De Campos, José M.; Kusak, Elena M.; Landa, Iñigo; Leskelä, Susanna; Montero-Conde, Cristina; Leandro-García, Luis J.; Vallejo, Luis A.; Madrigal, Beatriz; Rodríguez-Antona, Cristina; Robledo, Mercedes; Cascón, Alberto (Clinical endocrinology (Oxford), 2008)
Summary Head and neck paragangliomas are usually asymptomatic and benign tumours arising mainly from the carotid body and the vagal, tympanic or jugular glomus. The majority of patients develop sporadic masses, and around 30% of cases harbour germline mutations in one of the succinate dehydrogenase genes: SDHB, SDHC or SDHD. In these hereditary cases, the presence of familial antecedents of the disease, multiplicity/bilaterality, young age at onset, and more recently, presence of gastrointestinal stromal tumours, are main factors to be considered. Here we describe a new mutation (c.256–257insTTT) affecting the SDHC gene in a 60‐year‐old‐patient with a single head and neck paraganglioma, and without familial antecedents of the disease. In silico splice site analysis showed that this variant created a cryptic splice acceptor site and loss of heterozygosity (LOH) supported the pathogenic role of the mutation. Control population analyses did not detect this variant but revealed a novel SDHC polymorphism that exhibited a frequency of 0·3% (3/1020). This latter finding highlights the importance of assessing the clinical relevance of variants of unknown significance by means of analysing sufficient controls. Despite having found a germline mutation in an older, apparently sporadic patient, we consider that the high costs of analysing all susceptibility genes related to the disease support the recommendation of screening for mutations only in patients fulfilling the above criteria.